Parental emotional warmth and identity integration among Chinese migrant adolescents: The role of hope. (September 2017) - Ni, Shiguang; Chui, Cheryl Hiu-Kwan; Ji, Xiaowen; Li, Hong; Chan, Lai-Wan Cecilia
Literature has established that migration processes have significant effects on the mental and psychological health of migrant children and adolescents. Yet, little is known of the effects of family dynamics and individual characteristics on rural-to-urban migrant adolescents' psychological adjustment in the context of China. Using a cross-sectional questionnaire-based research design, this article examines the relationship between perceived parental emotional warmth, identity integration and hope among a group of Chinese migrant adolescents. Of a sample of 1, 345 Chinese migrant adolescents, between 11 and 19 years old, we found that perceived parental emotional warmth was significantly associated with identity integration, and that hope partially mediated the relationship between parental emotional warmth and identity integration. The implications of the findings for migrant adolescents' psychological adjustment in receiving communities are discussed.